(untitled) (Revista Brasileira Multidisciplinar, 2008)
This paper presents a brief approach on environmental aspects related to the development of agriculture in the world and especially in Brazil, detaching some historical aspects. Some characteristics of the social and environmental degradation generated by the processes of production of modern agriculture, based on studies of Environmental Sciences, in general, and, more specifically, of Agroecology, are presented, as well as the necessity of searching for new models of development according to the recent paradigm of sustainability (social, economic and environmental), debated in international conferences on ’environment and development’.